Pkm Project-Based Pjok Learning In The Implementation Of The Independent Curriculum In Indonesian Schools In Riyadh - Dwi Cahyo Kartiko; Gigih Siantoro; Abdul Rachman Syam Tuasikal; Heryanto Nur Muhammad; Taufiq Hidayat; Muhammad Muhammad; Heri Wahyudi; Bayu Budi Prakoso; Suryanto Agung Prabowo; Eva Ferdita Yuhantini; Muhammad Wahyu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Indonesian Schools Overseas (SILN) encounter difficulties when it comes to applying the Merdeka Curriculum, especially at the Indonesian School Riyadh (SIR) located in Saudi Arabia. Key challenges for Physical Education, Sport, and Health (PJOK) educators include limited human resources, inadequate infrastructure, and the need for cultural adaptation. This community service (PkM) initiative seeks to improve the skills of PJOK teachers at SIR via training in Project Based Learning (PjBL) that fits within the Merdeka Curriculum guidelines. The approach used involved assessing needs, preparing materials, providing theoretical instruction, conducting simulations, and gathering feedback. The event took place on September 29, 2024, at the Indonesian School Riyadh, with participation from two educators from FIKK Unesa, one PJOK instructor, and six student-teachers. Evaluation findings indicated excellent performance in all areas: materials (94%), organization (96%), facilities (90%), and instructor expertise (98%), culminating in an overall average of 95%. The results include publications in mass media and a poster registered with HKI. This PkM initiative has made a significant contribution to enhancing the abilities of PJOK teachers in applying PjBL to boost students' daily physical activity in accordance with the principles of the Merdeka Curriculum.